Estimating the NAIRU in Australia - Heather Ruberl; Meika Ball; Larissa Lucas; Thomas Williamson (The Australian Government, The Treasury, 2021)
The Non-Accelerating Inflation Rate of Unemployment (NAIRU) is a variable of interest to policy makers as it provides an estimate of the degree of labour market slack in the economy. However, the NAIRU is unobservable, and must be estimated using statistical models. This is most commonly undertaken within the Phillips curve framework, which estimates the relationship between price or wage growth and unemployment. This is a key equation for understanding economic conditions, and is used to forecast wages growth at the Australian Treasury. Australia's NAIRU was previously thought to be around 5 per cent. We have considered a range of alternative specifications for estimating the wage Phillips curve, and this working paper details Treasury's updated model. We consider specification choices that include: updating the measures of inflation and inflation expectations; the introduction of a productivity gap term; the inclusion of a structural break to allow for the flattening of the Phillips curve; and other changes to bring the model more in-line with the recent literature. The updated model produces estimates of the NAIRU between 4.5 and 5 per cent over the last few years immediately prior to the COVID-19 recession.
Keywords: E24; E31; 330; NAIRU; Phillips Curve; Inflationary Expectations